Adherence to HIV antiretroviral therapy among pregnant and postpartum women during the Option B+ era: 12-month cohort study in urban South Africa and rural Uganda - Matthews, Lynn T.; Orrell, Catherine; Mwebesa, Bosco Bwana; Tsai, Alexander C.; Psaros, Christina; Asiimwe, Stephen; Amanyire, Gideon; Musinguzi, Nicholas; Bell, Kathleen; Bangsberg, David R.; Haberer, Jessica E. (Journal of the International AIDS Society, 2020)
We conducted a cohort study to understand patterns of anti-retroviral therapy (ART) adherence during pregnancy, postpartum and non-pregnancy follow-up among women initiating ART in public clinics offering Option B+ in rural Uganda and urban South Africa. We collected survey data, continuously monitored ART adherence (Wisepill), HIV-RNA and pregnancy tests at zero, six and twelve months from women initiating ART in Uganda and South Africa, 2015 to 2017. The primary predictor of interest was follow-up time categorized as pregnant (pregnancy diagnosis to pregnancy end), postpartum (pregnancy end to study exit) or non-pregnancy-related (neither pregnant nor postpartum). Fractional regression models included demographics and socio-behavioural factors informed by the Behavioral Model for Vulnerable Populations. We evaluated HIV-RNA at 12 months by ever- versus never-pregnant status. In Uganda, 247 women contributed 676, 900 and 1274 months of pregnancy, postpartum and non-pregnancy-related follow-up. Median ART adherence was consistently ≥90%: pregnancy, 94% (interquartile range [IQR] 78,98); postpartum, 90% (IQR 70,97) and non-pregnancy, 90% (IQR 80,98). Poorer adherence was associated with younger age (0.98% [95% CI 0.33%, 1.62%] average increase per year of age) and higher CD4 cell count (1.01% [0.08%, 1.94%] average decrease per 50 cells/ mm3). HIV-RNA was suppressed among 91% (N = 135) ever-pregnant and 86% (N = 85) never-pregnant women. In South Africa, 190 women contributed 259, 624 and 1247 months of pregnancy, postpartum and non-pregnancy-related follow-up. Median adherence was low during pregnancy, 74% (IQR 31,96); postpartum, 40% (IQR 4,65) and non-pregnancy, 77% (IQR 47,92). Poorer adherence was associated with postpartum status (22.3% [95%CI 8.6%, 35.4%] average decrease compared to non-pregnancy-related follow-up) and less emotional support (1.4% [0.22%, 2.58%] average increase per unit increase). HIVRNA was suppressed among 57% (N = 47) ever-pregnant and 86% (N = 93) never-pregnant women. Women in rural Uganda maintained high adherence with 91% of ever-pregnant and 86% of never-pregnant women suppressing HIV-RNA at 12 months. Women in urban South Africa struggled with adherence, particularly during postpartum follow-up with median adherence of 40% and 57% of women with HIV-RNA suppression at one year, suggesting a crisis for postpartum women with HIV in South Africa. Findings suggest that effective interventions should promote emotional support.
Keywords: Adherence; ARV; Cohort studies; Gender; Africa < Region; Women; HIV